Iron monatomic catalyst with axial modification and preparation method and application thereof

The iron single-atom catalyst, modified by axial phosphate coordination on cellulose-derived catalytic activated carbon, solves the problem of insufficient precision control of single-atom catalysts in the prior art, achieving high activity, selectivity and stable zinc-air battery performance, and reducing costs.

CN121460601APending Publication Date: 2026-02-03ZHENGZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511620545.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-07
Publication Date
2026-02-03

AI Technical Summary

Technical Problem

Existing technologies struggle to prepare highly active, selective, and stable single-atom catalysts, especially in zinc-air batteries. Traditional synthesis methods lack precise control, leading to decreased catalytic performance. Noble metal catalysts are also costly and lack stability.

Method used

Using an iron single-atom catalyst, axial phosphate coordination modification was performed on cellulose-derived catalytic activated carbon. Phytic acid was used as a chelating agent to precisely control the chemical environment of the iron single atom. Combined with hydrothermal and calcination processes, a FeN4/CC structure with axial PO4 groups was formed.

Benefits of technology

It improves catalytic activity, selectivity, and stability, enhances the peak power density and cycle stability of zinc-air batteries, and has a lower cost than precious metal catalysts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121460601A_ABST
    Figure CN121460601A_ABST
Patent Text Reader

Abstract

The invention discloses an iron monatomic catalyst with axial modification and a preparation method and application thereof, and belongs to the technical field of catalysts for battery positive electrodes. A preparation method of an iron monatomic catalyst with axial modification comprises the following steps: mixing an iron source, dimethylimidazole and ammonium chloride in an alcohol organic solvent, and then adding cellulose to obtain a mixed solution; carrying out a hydrothermal reaction on the mixed solution, and after the hydrothermal reaction is finished, carrying out first calcination in an inert gas atmosphere to obtain FeN4 / CC; carrying out chelating treatment on FeN4 / CC by taking phytic acid as an etching agent to obtain a chelated product; and calcining for the second time in an inert gas atmosphere to obtain the iron monatomic catalyst with axial modification. The catalyst prepared by the invention has extremely high ORR catalytic activity, has very good power density and cycle life when being used as a zinc-air battery cathode catalyst, and is an innovation in the aspect of catalysts for zinc-air electrodes.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of battery positive electrode catalysts, and more particularly to an iron single-atom catalyst with axial modification and a preparation method and application thereof. BACKGROUND

[0002] With the increasing demand for energy and the intensifying energy shortage, the development of innovative renewable energy systems has become increasingly urgent. Among various emerging energy storage technologies aimed at reshaping the energy landscape, zinc-air batteries (ZABs) have emerged as a promising contender. The appeal of ZABs lies in their high theoretical energy density, inherent safety, and environmental-friendly characteristics. The core of ZABs' efficacy is the efficiency of the oxygen reduction reaction (ORR) at the air electrode. This efficiency depends on the quality and activity of the catalyst used. Therefore, the development of high-activity, stable, and high-selectivity ORR catalysts has become a key and timely research area. Moreover, the significance of advancing ORR catalyst research extends far beyond ZABs, as the ORR also plays a crucial role in fuel cells and other metal-air batteries.

[0003] The inherent limitations of traditional materials have constrained the pursuit of high-efficiency ORR catalysts. Noble metals are hindered by high costs and stability issues, transition metal compounds are often poorly durable, and carbon-based catalytic systems often lack well-defined active sites. These challenges have heightened researchers' interest in single-atom catalysts (SACs) as a promising alternative. However, several key obstacles still hinder their practical application. Metastable, surface-bound metal atoms often aggregate under operating pressures, and insufficient control over the oxygen activation pathway limits the selectivity of the four-electron (4e - ) ORR. 4e - The ORR is a critical operational requirement for ZABs, necessitating strict suppression of peroxide byproducts to avoid chemical energy loss and mitigate cathode degradation. Furthermore, current synthesis methods lack the atomic-level precision required to design metal coordination environments that can simultaneously optimize adsorption energetics and charge transfer kinetics. Addressing these challenges requires breakthroughs in stabilizing isolated metal centers through advanced anchoring strategies.

[0004] With the establishment of structure-property relationships at sub-angstrom resolution, emerging strategies for optimizing SACs increasingly emphasize axial coordination engineering to precisely tune catalytic active sites. Compared to single-atom planar doping, axial coordination provides excellent three-dimensional electronic modulation while maintaining structural stability. However, achieving precise control over the first-shell coordination environment remains technically challenging. Although advanced characterization techniques have confirmed that sub-angstrom level changes in axial ligands can lead to significant electronic reconstructions, there are still major gaps in understanding their dynamic behavior under operating conditions, particularly regarding long-term ligand stability and transient intermediate interactions. From a preparation technology perspective, current mainstream synthetic strategies more generally face problems such as insufficient coordination precision, poor structural uniformity, and catalytic performance degradation.

[0005] High-temperature pyrolysis is currently the most commonly used method for preparing axially coordinated single-atom catalysts. It primarily achieves the binding of metal sites and axial ligands through the high-temperature carbonization of precursors (such as metal-organic frameworks (MOFs) and nitrogen-containing carbon precursors). However, this method has significant inherent drawbacks. At high temperatures (typically 800℃~1100℃), carbon skeleton reconstruction, organic ligand decomposition, and heteroatom rearrangement occur simultaneously, making it difficult to precisely control the type (O, N, S), quantity, and bond length of axial ligands. This directly affects the electronic environment of the catalytic active sites and the catalytic efficiency. Compared to high-temperature pyrolysis, the simpler wet chemical method can prepare catalysts through the coordination reaction of metal precursors and ligand molecules in solution. However, it also faces insurmountable precision limitations. Solvent molecules (such as methanol and water) and counterions (such as Cl-) in the solution can significantly affect the catalyst's performance. - SO4 2- This may lead to competition with the target axial ligand for binding to the metal center, resulting in a "multi-ligand hybridization" phenomenon. These defects can reduce the catalytic performance of single-atom catalysts, including decreased catalytic activity, selectivity, and stability. Summary of the Invention

[0006] To address the above problems, this invention provides an axially modified iron single-atom catalyst, its preparation method, and its application. The axially modified iron single-atom catalyst prepared according to the method of this invention exhibits excellent catalytic activity, selectivity, and stability.

[0007] The first objective of this invention is to provide a method for preparing an axially modified iron single-atom catalyst, comprising the following steps: Iron source, dimethylimidazole and ammonium chloride are mixed in an alcohol-based organic solvent. During the mixing process, a coordination reaction takes place. After the reaction is completed, cellulose is added to obtain a mixed solution.

[0008] The mixture was subjected to a hydrothermal reaction. During the hydrothermal process, cellulose served as a matrix to fix the complex formed by iron and dimethylimidazole. After the hydrothermal reaction was completed, a first calcination was carried out under an inert gas atmosphere. During the first calcination, the Fe metal sites were dispersed in the carbon support formed by cellulose to obtain FeN4 / CC.

[0009] Phytic acid was used as a chelating agent to treat FeN4 / CC, which caused phytic acid and iron to chelate and form a coordination complex, thus obtaining the chelated product.

[0010] A second calcination was carried out under an inert gas atmosphere. During the second calcination, the coordination complex decomposed to form FeN4 containing axial PO4 groups, resulting in the axially modified iron single-atom catalyst P-FeN4 / CC.

[0011] In a preferred embodiment of the present invention, during the chelation treatment, FeN4 / CC and phytic acid aqueous solution are mixed, with the ratio of FeN4 / CC to phytic acid aqueous solution being 1g: 5mL~6mL, and the mass concentration of phytic acid aqueous solution being 70%.

[0012] In a preferred embodiment of the present invention, the chelation treatment method is: stirring at room temperature for 2 to 3 hours.

[0013] In a preferred embodiment of the present invention, the mass ratio of iron source to dimethylimidazole is 1:1.5~2.

[0014] The mass ratio of iron source to ammonium chloride is 1:25~30.

[0015] The mass ratio of iron source to cellulose is 1:10~15.

[0016] In a preferred embodiment of the present invention, the hydrothermal reaction is carried out at a temperature of 120°C to 140°C and for a reaction time of 10 to 12 hours.

[0017] In a preferred embodiment of the present invention, the calcination temperature during the first calcination is 800℃~900℃ and the calcination time is 2h~2.5h.

[0018] In a preferred embodiment of the present invention, the calcination temperature during the second calcination is 300℃~350℃ and the calcination time is 1.5h~2h.

[0019] A second objective of this invention is to provide an axially modified iron single-atom catalyst, prepared using the method described above. The axially modified iron single-atom catalyst consists of Fe-NC single atoms with axial phosphate coordination modification uniformly dispersed in cellulose-derived catalytic activated carbon. Axial phosphate accelerates the dynamic configurational transformation of Fe sites during the reaction, enhancing the kinetics of the ORR catalytic reaction.

[0020] A third objective of this invention is to provide the application of the aforementioned axially modified iron single-atom catalyst as an ORR catalyst for the positive electrode of a zinc-air battery. The zinc-air battery includes a negative electrode, a positive electrode, and an electrolyte. The negative electrode can be a zinc sheet, and the positive electrode consists of an ion-exchange membrane, nickel foam, a catalyst layer, and a gas diffusion layer. The catalyst layer is formed by loading the axially modified iron single-atom catalyst prepared according to this invention at a loading of 1 mg·cm³. -2 It was obtained by coating carbon paper. The electrolyte was a 6M KOH aqueous solution (containing 0.2 M Zn(OAc)2).

[0021] Compared with the prior art, the present invention has the following beneficial effects: (1) This invention uses iron single-atom FeN4 as a template and selects phytic acid for chemical chelation. Phytic acid, as an effective chelating agent, can strongly bind to single-atom iron, thereby precisely controlling its surrounding chemical environment. This process ensures that the axial coordination phosphate modification of single-atom iron on the catalyst is achieved, allowing for fine adjustment of the electronic environment of the generated single-atom structure. This strategy helps improve the performance of single-atom catalysts, including their catalytic activity, selectivity, and stability, because axial phosphate modification can effectively regulate the electronic structure of iron single atoms and their behavior under reaction conditions. This method overcomes the shortcomings of insufficient precision control in traditional synthesis methods, further promoting the development and application of high-performance single-atom catalysts.

[0022] (2) This invention innovatively synthesizes a single-atom catalyst based on natural wood cellulose-derived catalytic activated carbon. The abundant specific surface area and porous structure of the cellulose-derived carbon enable the uniform dispersion of single-atom sites and maintain structural stability during catalysis.

[0023] (3) This invention optimizes the four-electron reaction pathway of ORR by precisely modifying the axial phosphate coordination of single-atom iron sites, thereby driving the transformation of catalyst spin and crystal field coordination mode during catalysis, and improving ORR reaction activity and stability.

[0024] (4) The P-FeN4 / CC prepared in this invention has extremely high ORR catalytic activity, selectivity and stability. Liquid and quasi-solid-state zinc-air batteries assembled using it as the positive electrode catalyst of zinc-air batteries have superior peak power density and cycle stability.

[0025] (5) The preparation method of the present invention has low cost and the prepared product has good performance. The P-FeN4 / CC catalyst prepared by non-precious metals has extremely high ORR catalytic activity and zinc-air battery application effect, which is significantly better than the commercial catalyst Pt / C-20% + RuO2 prepared by precious metals. Attached Figure Description

[0026] Figure 1 This is a schematic diagram illustrating the preparation of an axially modified iron single-atom catalyst according to the present invention.

[0027] Figure 2 X-ray powder diffraction patterns of NCC, FeN4 / CC, and P-FeN4 / CC.

[0028] Figure 3 The images shown are SEM, TEM, and AC HAADF-STEM images of P-FeN4 / CC prepared in Example 1. Image a is a scan of P-FeN4 / CC prepared in Example 1 at a scale bar of 50 μm; image b is a scan of P-FeN4 / CC prepared in Example 1 at a scale bar of 5 μm; image c is a TEM image of P-FeN4 / CC prepared in Example 1, where the inset in image c is a magnified view and a selected area electron diffraction image; image d is an AC HAADF-STEM image of P-FeN4 / CC prepared in Example 1; image e is a magnified view of image d; image f is the atomic intensity distribution map of site A and site B in image e; and image g is the energy-dispersive X-ray spectrum of P-FeN4 / CC.

[0029] Figure 4 In the diagram, a represents the FTIR spectra of different samples, b represents the EPR spectra of different samples, c represents the temperature-varying magnetization curves of different samples, d represents the normalized iron K-edge XANES spectra of different samples, and e represents the Fourier transform k-axis of different samples. 3 Weighted Fe K-edge EXAFS spectrum, f is the experimental and fitting curve of EXAFS spectrum of different samples in R space, the inset in f is the model diagram of P-FeN4 / CC and FeN4 / CC respectively, g is the wavelet transform diagram of P-FeN4 / CC prepared in Example 1, h is the wavelet transform diagram of FeN4 / CC prepared in Example 1, and i is the wavelet transform diagram of Fe-foil.

[0030] Figure 5 In the figure, a is the half-wave potential diagram of different catalysts, b is the hydrogen peroxide yield and electron transfer number analysis diagram of different catalysts, the inset in b is the disk current and ring current analysis of the ring disk current test, and c is the current retention rate diagram of the long-term stability test of different catalysts.

[0031] Figure 6In the diagram, a shows the discharge polarization curve and power density graph of the flexible ZAB assembled from P-FeN4 / CC prepared in Example 1; b shows the cyclic charge-discharge test of the flexible ZAB assembled from P-FeN4 / CC prepared in Example 1 (the inset in b is a schematic diagram of solid-state ZAB assembly); c shows the power density graph of the liquid ZAB assembled from P-FeN4 / CC prepared in Example 1; and d shows the cyclic charge-discharge test of the liquid ZAB assembled from P-FeN4 / CC prepared in Example 1. Detailed Implementation

[0032] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0033] According to the preparation method of this invention, phytic acid with strong chelating properties achieves axial coordination phosphate modification of iron single atoms, avoiding the problems of poor ORR reaction activity, selectivity, and stability of conventional metal single-atom catalysts. In addition, the use of non-noble metal iron in this invention avoids the problem of poor power density and cycle stability of zinc-air batteries caused by insufficient ORR activity and stability of noble metal catalysts. The regulation effect of conventional transition metal single-atom catalysts is not good, and the mechanism is still unclear. The axially modified iron single-atom catalyst prepared by this invention drives the transformation of catalyst spin and crystal field coordination mode during catalysis by precisely modifying the axial coordination of single-atom iron single-atom sites, thereby optimizing the four-electron reaction pathway of ORR and improving ORR reaction activity, selectivity, and stability.

[0034] The cellulose used in this invention is cellulose extracted from natural wood, specifically purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., with product number C104842 and CAS number 9004-34-6.

[0035] Example 1 This embodiment provides a method for preparing an axially modified iron single-atom catalyst, which is prepared according to the following steps: S1: 0.2g FeCl3·6H2O, 0.3g dimethylimidazole, and 5g ammonium chloride were stirred vigorously in 50mL methanol solution for 30min to obtain a mixed solution.

[0036] S2: Under magnetic stirring, 2g of cellulose was added to the mixture obtained in S1. After stirring for 30min at 1000rpm, the mixture was transferred to a high-pressure reactor and reacted at 120ºC for 12h. After cooling to room temperature, the mixture was removed, washed with methanol and water, and dried to obtain a hydrothermal sample.

[0037] S3: Place the hydrothermal sample obtained in S2 into a tube furnace and heat it under an Ar atmosphere at 5°C. o The temperature was increased from room temperature to 900℃ at a rate of C / min, and held at that temperature for 2 hours to obtain FeN4 / CC.

[0038] S4: Weigh 100 mg of FeN4 / CC and disperse it in 20 mL of aqueous solution. Add 0.5 mL of phytic acid aqueous solution with a mass concentration of 70%. Stir at room temperature for 2 h, then centrifuge, wash and dry to obtain the chelated product.

[0039] S5: Place the chelated product obtained in S4 into a tube furnace and heat it under an Ar atmosphere at 2... o The P-FeN4 / CC catalyst was prepared by heating from room temperature to 300℃ and holding at that temperature for 2 hours at a rate of C / min.

[0040] The axially modified iron single-atom catalyst prepared by this invention has the molecular formula P-FeN4 / CC and the structure is highly dispersed Fe-NC single atoms uniformly dispersed in forest cellulose-derived catalytic activated carbon with axial phosphate coordination modification.

[0041] Example 2 This embodiment provides a method for preparing an axially modified iron single-atom catalyst, which is prepared according to the following steps: S1: 0.2g FeCl3·6H2O, 0.35g dimethylimidazole, and 6g ammonium chloride were stirred vigorously in 50mL methanol solution for 30min to obtain a mixed solution.

[0042] S2: Under magnetic stirring, 2.5g of cellulose was added to the mixture obtained in S1. After stirring at 1000rpm for 30min, the mixture was transferred to a high-pressure reactor and reacted at 140ºC for 10h. After cooling to room temperature, the mixture was removed, washed with methanol and water, and dried to obtain a hydrothermal sample.

[0043] S3: Place the hydrothermal sample obtained in S2 into a tube furnace and heat it under an Ar atmosphere at 5°C. o The temperature was increased from room temperature to 800℃ at a rate of C / min, and held at that temperature for 2.5 h to obtain FeN4 / CC.

[0044] S4: Weigh 100 mg of FeN4 / CC and disperse it in 20 mL of aqueous solution. Add 0.6 mL of 70% phytic acid solution. Stir at room temperature for 3 h, then centrifuge, wash and dry to obtain the chelated product.

[0045] S5: Place the chelated product obtained in S4 into a tube furnace and heat it under an Ar atmosphere at 2... o The P-FeN4 / CC catalyst was prepared by heating from room temperature to 350℃ and holding at that temperature for 1.5 h at a rate of C / min.

[0046] Example 3 This embodiment provides a method for preparing an axially modified iron single-atom catalyst, which is prepared according to the following steps: S1: 0.2g FeCl3·6H2O, 0.4g dimethylimidazole, and 5.5g ammonium chloride were stirred vigorously in 50mL methanol solution for 30min to obtain a mixture.

[0047] S2: Under magnetic stirring, 3g of cellulose was added to the mixture obtained in S1. After stirring for 30min at 1000rpm, the mixture was transferred to a high-pressure reactor and reacted at 130ºC for 11h. After cooling to room temperature, the mixture was removed, washed with methanol and water, and dried to obtain a hydrothermal sample.

[0048] S3: Place the hydrothermal sample obtained in S2 into a tube furnace and heat it under an Ar atmosphere at 5°C. o The temperature was increased from room temperature to 850℃ at a rate of C / min, and held at that temperature for 2.3 h to obtain FeN4 / CC.

[0049] S4: Weigh 100 mg of FeN4 / CC and disperse it in 20 mL of aqueous solution. Add 0.65 mL of 70% phytic acid solution. Stir at room temperature for 2.5 h, then centrifuge, wash and dry to obtain the chelated product.

[0050] S5: Place the chelated product obtained in S4 into a tube furnace and heat it under an Ar atmosphere at 2... o The P-FeN4 / CC catalyst was prepared by heating from room temperature to 330℃ and holding at that temperature for 1.8 h at a rate of C / min.

[0051] Comparative Example 1 This comparative example provides a method for preparing N-doped cellulose-derived carbon, which is prepared according to the following steps: S1: Stir 5g of ammonium chloride in 50mL of methanol solution for 30min.

[0052] S2: Under magnetic stirring, add 2g of cellulose to the solution obtained in S1, stir for 30min, transfer to a high-pressure reactor, react at 120ºC for 12h, cool to room temperature, remove, wash with methanol and water, and dry.

[0053] S3: Place the sample obtained in S2 into a tube furnace and heat it under an Ar atmosphere at 5°C. o The temperature was increased from room temperature to 900℃ at a rate of C / min, and held at that temperature for 2 hours to obtain NCC.

[0054] Comparative Example 2 This comparative example provides a method for preparing an iron single-atom catalyst, which is carried out according to the following steps: S1: Mix 0.2g FeCl3·6H2O, 0.3g dimethylimidazole, and 5g ammonium chloride in 50mL of methanol solution and stir vigorously for 30min.

[0055] S2: Under magnetic stirring, add 2g of cellulose to the solution obtained in S1, stir for 30min, transfer to a high-pressure reactor, react at 120ºC for 12h, cool to room temperature, remove, wash with methanol and water, and dry.

[0056] S3: Place the sample obtained in S2 into a tube furnace and heat it under an Ar atmosphere at 5°C. o The temperature was increased from room temperature to 900℃ at a rate of C / min, and held at that temperature for 2 hours to obtain FeN4 / CC.

[0057] Figure 1 This is a schematic diagram of the synthesis of the catalyst P-FeN4 / CC prepared in Example 1. In the experimental synthesis, Fe was constructed by anchoring isolated iron single-atom active sites using the unique fibrous structure of cellulose as a matrix. Initially, dimethylimidazole provided coordination for a specific structure, ammonium chloride served as a nitrogen source and weakly acidic etching of cellulose, increasing the specific surface area of ​​cellulose. Iron coordinated with dimethylimidazole and embedded within the cellulose framework. During the first calcination, dimethylimidazole coordination was used to stabilize the iron metal center, and the Fe metal sites were dispersed in the carbon support formed by cellulose, resulting in FeN4 / CC. Next, phytic acid was introduced as a phosphorus-containing chelating agent to coordinate with the dispersed iron atoms, forming a strong chelating interaction between phytic acid and the iron center. Finally, the complex underwent calcination again. During the second calcination, the coordination complex was transformed into a highly stable FeN4 catalytic structure with axial PO4 groups (denoted as P-FeN4 / CC). The axial PO4 groups formed by the thermal decomposition of phytic acid are incorporated into the FeN4 microenvironment, inducing electronic modulation and enhancing structural stability.

[0058] Figure 2XRD characterization of the catalyst P-FeN4 / CC prepared in Example 1 and the catalysts prepared in Comparative Examples 1 and 2. The XRD patterns show that NCC, FeN4 / CC, and P-FeN4 / CC exhibit typical amorphous carbon crystal structures. The two broad diffraction peaks at 23° and 43° correspond to the (002) and (101) crystal planes of carbon, respectively. This demonstrates that the FeN4 / CC and P-FeN4 / CC catalysts do not contain aggregated metal particles and exist as monodisperse metal sites. Figure 2 In this context, 2θ is denoted as 2 theta, and intensity is denoted as Intensity.

[0059] Figure 3 SEM (a, b), TEM (c), and AC HAADF-STEM (d~g) images of the catalyst P-FeN4 / CC prepared in Example 1. The SEM images of P-FeN4 / CC show a spindle-shaped natural wood cellulose structure. Figure 3 (a) At a larger magnification, a dense porous structure is revealed on the fiber surface. Figure 3 (b) TEM images of P-FeN4 / CC show a large amount of amorphous carbon in the catalyst and in partially magnified TEM and selected area electron diffraction images, with no discernible metal lattice, proving that there is no metal agglomeration in the catalyst. Figure 3 c). AC HAADF-STEM images reveal the dispersed arrangement of isolated metallic bright spots (marked in yellow) in the P-FeN4 / CC catalyst. Figure 3 (d and e in the text). The spacing between the metal sites is approximately 0.25 nm to 0.26 nm. Figure 3 f in the figure. The corresponding energy-dispersive X-ray spectroscopy shows that Fe, N, C, P and O elements are uniformly dispersed in the P-FeN4 / CC catalyst. Figure 3 g in the middle.

[0060] Figure 4 FTIR (a), EPR (b), and XAS (c, d) characterization of the catalyst prepared in Example 1. FTIR showed a distinct absorption peak in the 900–1100 cm⁻¹ range, which is closely related to the stretching vibrations of the P–O and P–O–C bonds in C–N, C–O–C, and phosphorus-containing compounds (especially the PO₄ group). Compared with FeN₄ / CC, the successful introduction of PO₄ and its interaction with the carbon framework and iron active sites resulted in a strong absorption signal in this region for P-FeN₄ / CC. Figure 4 (a) EPR tests show that the axial PO4 ligands introduce additional ligand field components, facilitating electron transfer from Fe atoms to the highly electronegative PO4 groups. This electron redistribution enhances the paramagnetism of the iron species and alters the g-factor ( Figure 4 (b) in the middle.

[0061] X-ray absorption near-edge (XANES) analysis of the Fe K-edge of 0-FeN4 / CC showed that its absorption edge position was between that of the divalent iron standard iron phthalocyanine (FePc) and the trivalent iron standard iron oxide (Fe2O3), which have a FeN4 structural model, and higher than that of the FeN4 / CC sample. (The iron foil (Fe-foil) represents zero-valent metallic iron Fe.) 0 The standard sample). The higher absorption edge position of P-FeN4 / CC compared to FeN4 / CC indicates that the Fe species exist in a mixed oxidation state, with some charge transferred to the axial PO4 ( Figure 4 (c) Compared with FePc and FeN4 / CC, P-FeN4 / CC has a leading peak at 7114 eV (1s→4p along the plane symmetry direction). z The decrease in the characteristics of the transition indicates that the coordination of PO4 induced a transition from the D4h symmetry of FeN4 / CC to the C4v configuration of P-FeN4 / CC. Figure 4 (d) Fourier transform extended X-ray absorption fine structure (FT-EXAFS) provides direct evidence for the atomic dispersion of the Fe species. The main peak at 1.48 Å corresponds to the first-shell Fe–N / O coordination, and no detectable Fe-Fe metallic bonds were observed in the range of 1.97 Å–2.5 Å, ruling out the presence of Fe nanoparticles or clusters. Figure 4 The R-space fitting results show that FeN4 / CC and P-FeN4 / CC exhibit contours consistent with the established model (e). Figure 4 f in the text). Wavelet transform (wt) analysis of EXAFS oscillations ( Figure 4 g~i) further verified the single-atom properties of P-FeN4 / CC and FeN4 / CC in three dimensions. The results were highly consistent with the conclusions of FT-EXAFS, confirming the successful synthesis of the single-atom structure of the catalyst.

[0062] Figure 4 In 'a', the wavelength is denoted as Wavenumber, and the transmittance is denoted as Transmittance. Figure 4 In b, the temperature is denoted as Temperature. Figure 4 In c, the magnetic field strength is denoted as Magnetic field, and the effective magnetic moment strength is denoted as μ. eff , Figure 5 In d, energy is denoted as Energy and intensity is denoted as Intensity.

[0063] The ORR catalytic performance of the catalyst was then tested.

[0064] The series of catalysts prepared in Example 1 were subjected to ORR electrochemical testing. Electrochemical tests were performed on a CHI760E electrochemical workstation. The sample slurry was coated onto a rotating disk electrode (RDE) or rotating disk electrode (RRDE) as the working electrode, a platinum wire electrode as the counter electrode, and a silver / silver chloride electrode (Ag / AgCl) as the reference electrode. A 0.1M KOH solution was used as the electrolyte. The voltage data were converted to vs. RHE using the following formula:

[0065] Preparation of catalyst slurry for ORR test: Place 4 mg of catalyst, 500 μL of ethanol, and 50 μL of Nafion in a centrifuge tube and sonicate for more than 30 min. During the test, add 15 µL of the slurry to the working electrode.

[0066] Figure 5 Experimental characterization of ORR for different catalysts, from Figure 5 As can be seen from a~c in the data, under the same conditions, P-FeN4 / CC exhibits the highest half-wave potential (0.93V) compared to other catalysts and Pt / C (20%) in the ORR reaction. Figure 5 (a) Extremely high four-electron ORR selectivity, with electron transfer numbers of 0.38–0.4 in the voltage range of 0.4 V–0.8 V, and hydrogen peroxide yield (η) as low as 1.1% ( Figure 5 (b) Excellent stability, with a relative current retention rate of 90.5% after 136 hours of stable operation. Figure 6 (c in the text)

[0067] The following tests the performance of zinc-air batteries prepared with catalysts. The P-FeN4 / CC catalyst prepared in Example 1 was used for zinc-air battery testing. A commercial catalyst, Pt / C (20 wt.% Pt carbon-supported), and RuO2 were physically mixed at a mass ratio of 1:1 as a control. For the liquid zinc-air battery test, a 99.9% pure zinc sheet (10 cm * 3 cm * 0.02 cm) was used as the negative electrode. The electrolyte was a 6 M KOH aqueous solution containing 0.2 M Zn(OAc)2. An ion-exchange membrane, nickel foam, and a catalyst coated with a loading of 1 mg / cm³ were used. -2 The positive electrode of the air electrode is prepared by compressing four components: carbon paper, gas diffusion layer, etc.

[0068] The flexible zinc-air battery uses PVA hydrogel that absorbs high concentrations of KOH solution as a solid electrolyte, zinc foil as the anode, carbon cloth coated with catalyst as the air electrode, and nickel foam as the current collector.

[0069] Figure 6 Performance characterization of flexible (a, b) and liquid (c, d) zinc-air batteries assembled from P-FeN4 / CC and Pt / C (20%) + RuO2. Figure 6 As can be seen from a and b in the figure, the flexible zinc-air battery assembled based on P-FeN4 / CC has a higher peak power density (81 mW·cm). -2 It can be stably cycled for 160 h (480 cycles). The commercial noble metal catalyst Pt / C (20%) + RuO2 has a peak power density of 57 mW·cm⁻¹. -2 Its cyclic stability is also poor.

[0070] from Figure 6 As can be seen from c and d in the figure, the liquid zinc-air battery assembled based on P-FeN4 / CC also has a high peak power density (280.1 mW cm⁻¹). -2 It can also operate stably for 11,130 cycles, which is far superior to precious metal-based catalysts.

[0071] Figure 6 In terms of a and c, voltage is denoted as Voltage, and power density is denoted as Power density. Figure 6 In b, the number of cycles is denoted as Number of cycles, and the voltage is denoted as Voltage. ​ In d, time is denoted as Time and voltage as Voltage.

[0072] Although preferred embodiments of the invention have been described, those skilled in the art, upon learning the basic inventive concept, can make other changes and modifications to these embodiments. Therefore, the appended claims are intended to be interpreted as including both the preferred embodiments and all changes and modifications falling within the scope of the invention.

[0073] Obviously, those skilled in the art can make various modifications and variations to this invention without departing from its spirit and scope. Therefore, if these modifications and variations fall within the scope of the claims of this invention and their equivalents, this invention also intends to include these modifications and variations.

Claims

1. A method for preparing an axially modified iron single-atom catalyst, characterized in that, Includes the following steps: Iron source, dimethylimidazole and ammonium chloride are mixed in an alcohol-based organic solvent. During the mixing process, a coordination reaction occurs. After the reaction is completed, cellulose is added to obtain a mixed solution. The mixture was subjected to a hydrothermal reaction. During the hydrothermal process, cellulose served as a matrix to fix the complex formed by iron and dimethylimidazole. After the hydrothermal reaction was completed, a first calcination was carried out under an inert gas atmosphere. During the first calcination, the Fe metal sites were dispersed in the carbon support formed by cellulose to obtain FeN4 / CC. Phytic acid was used as a chelating agent to chelate FeN4 / CC, so that phytic acid and iron chelate to form a coordination complex, and the chelated product was obtained. A second calcination was carried out under an inert gas atmosphere. During the second calcination, the coordination complex decomposed to form FeN4 containing axial PO4 groups, resulting in the axially modified iron single-atom catalyst P-FeN4 / CC.

2. The method for preparing the axially modified iron single-atom catalyst according to claim 1, characterized in that, During the chelation treatment, FeN4 / CC and phytic acid aqueous solution were mixed in a ratio of 1g:5mL~6mL, and the mass concentration of the phytic acid aqueous solution was 70%.

3. The method for preparing the axially modified iron single-atom catalyst according to claim 1, characterized in that, The chelation treatment method is to stir at room temperature for 2 to 3 hours.

4. The method for preparing the axially modified iron single-atom catalyst according to claim 1, characterized in that, The mass ratio of iron source to dimethylimidazole is 1:1.5~2; The mass ratio of iron source to ammonium chloride is 1:25~30; The mass ratio of iron source to cellulose is 1:10~15.

5. The method for preparing the axially modified iron single-atom catalyst according to claim 1, characterized in that, During the hydrothermal reaction, the reaction temperature is 120℃~140℃ and the reaction time is 10h~12h.

6. The method for preparing the axially modified iron single-atom catalyst according to claim 1, characterized in that, During the first calcination, the calcination temperature is 800℃~900℃ and the calcination time is 2h~2.5h.

7. The method for preparing the axially modified iron single-atom catalyst according to claim 1, characterized in that, During the second calcination, the calcination temperature is 300℃~350℃ and the calcination time is 1.5h~2h.

8. An axially modified iron single-atom catalyst, characterized in that, The catalyst was prepared by the method described in any one of claims 1 to 7, wherein the axially modified iron single-atom catalyst is Fe-NC single atoms with axial phosphate coordination modification uniformly dispersed in cellulose-derived catalytic activated carbon.

9. The application of the axially modified iron single-atom catalyst of claim 8 as an ORR catalyst for the cathode of a zinc-air battery.